Service Quality, Brand Image and its Impact on Customer Satisfaction Levels of Umrah Rabbanitour Travel in Bandung, West Java - Rizky Maidan Ilmy (Universitas Pendidikan Indonesia, 2020)
Business competition in the service sector it is getting tighter in this era. Focus on customer satisfaction by giving good service is one of the strategies to win the market competition. Cause in creating customer satisfaction, the company must be increasing value and image from its brand. The research method is used in this research is the explanatory method, and data collection is carried out using a questionnaire. The purpose of research is to know relation or service quality influences and brand image to customer satisfaction. The finding in this study is that there is a simultaneous effect (together) between quality service variable (X1) and brand image (X2) to customer satisfaction (Y). From double regression analysis linear result is getting significance value 0,000 that its value significance level value α (0,01). The result of analysis in this research has also shown the magnitude of service quality support (X1) and brand image (X2) variable who indicated by R Square value 0,868, that is mean service quality simultaneously (together) gives support to 86,8% while the rest 13,2% influenced by other variables not examined in this study.